The modelling of high-contrast photonic crystal slabs using the novel extension of the effective index method - Dems, Maciej; Nakwaski, Włodzimierz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
This paper presents a new approach to determination of the band structure in two-dimensional (2D) photonic crystal slabs using the enhanced effective index approximation. The proposed method remains valid in the wide frequency range even for high-index contrast heterostructures.
Optica Applicata, Vol. 36, 2006, nr 1, s. 51-56
Keywords: optyka; photonic crystal slabs; effective index method